Preparation and application of thermal activation modified polyaniline loaded cuprous oxide monolithic electrode
By thermal activation and growth CU-BTC in polyiline, the overall electrode electrode oxidized asian copper nanoparticles is formed, the problem of poor catalytic stability of copper-based electrical catalysts, improved catalytic efficiency and stability, and reduced the cost of preparation of the electrode.
Patent Information
- Application Number
- CN202411517543.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing copper-based electrocatalysts have poor stability during electrochemical reduction of carbon dioxide, resulting in reduced catalytic activity and it is difficult to maintain the pre-designed active site structure.
The thermal activation polyiline is used as the middle layer, and the CU-BTC is growing on its surface through the original sedimentation method, forming an overall electrode oxidized asian copper nanoparticles, increasing the load and active sites of the copper-based catalyst.
It improves the stability and catalytic efficiency of the electrocatalyst, enhances the carbon dioxide conversion performance, avoids the problem of material shedding caused by the binder, and reduces the cost of electrode preparation.
Smart Images

Figure CN119332279A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical reduction technology, and in particular to the preparation of a thermally activated polyaniline-modified cuprous oxide nanoparticle monolithic electrode for electrocatalytic reduction of carbon dioxide. Technical Background
[0002] Converting carbon dioxide into high-value chemicals can effectively alleviate the dual pressures of greenhouse gas emissions and increased energy demand. Compared with other technologies, carbon dioxide electrocatalytic reduction technology is a highly potential negative carbon technology that uses renewable electricity to drive the reaction and convert carbon dioxide into carbon-based fuels, achieving energy storage and utilization and improving the level of energy consumption. Due to the stable molecular structure of carbon dioxide, activated CO2 is converted to CO2 -· A large energy barrier needs to be overcome. The carbon dioxide reduction process involves a multi-electron proton conversion process, and the product selectivity is poor, which limits the development of industrial production. Therefore, the need to develop stable and efficient electrocatalysts has become the key and difficult problem of electrocatalytic carbon dioxide.
[0003] Copper-based catalysts have unique electronic structures and rich valence states. They can produce high-value hydrocarbons during the electrochemical reduction of carbon dioxide and have attracted widespread attention. However, due to its unique structure, metallic copper often undergoes uncontrollable reconstruction during electrochemical reactions, making it difficult to maintain the pre-designed active site structure, resulting in reduced catalytic activity. Therefore, the coordination effect of organic ligands in copper metal organic frameworks can effectively protect the active sites from being destroyed.
[0004] In addition, a large amount of binder is added to the traditional copper-based catalyst electrode during the preparation process, and a large amount of catalyst is easy to agglomerate, thereby blocking the active sites inside the catalyst and reducing the catalytic activity. Compared with powder catalysts, the catalytic components are grown on the surface of the conductive substrate by in-situ deposition, and no additional binder and conductive agent are required, which accelerates the charge transfer rate and improves the catalytic efficiency. Since the particle size of Cu-BTC is large, it is directly grown by chemical deposition, and the loading amount of the catalyst is small, so the intermediate layer is introduced to solve the loading problem of the catalyst. Polyaniline is a common conductive material, and the amine groups in the polymer can be complexed with copper ions, which is beneficial to increase the loading amount of copper ions. Generally, the conductivity of polyaniline is enhanced by changing the acid concentration, and it is not seen that polyaniline is activated by pyrolysis to improve the conductivity of polyaniline and play the role of modifying cuprous oxide. First, polyaniline is deposited by electrodeposition, and Cu-BTC is deposited on the surface of polyaniline by in-situ deposition. Polyaniline is activated at low temperature and divalent copper ions are reduced to cuprous oxide. Summary of the invention
[0005] In view of the poor stability of existing copper-based electrocatalysts, a method for preparing a thermally activated polyaniline-modified cuprous oxide nanoparticle monolithic electrode for electrocatalytic reduction of carbon dioxide is provided. The method uses polyaniline as an intermediate layer to increase the loading amount of the copper-based catalyst on the conductive substrate, increase the number of active sites, and enhance the carbon dioxide conversion performance. The coordination effect in the metal organic framework prevents Cu 2+ The problem of being reduced in the electrochemical reaction is improved to improve the stability of the catalyst.
[0006] The present invention adopts a method for preparing a thermally activated polyaniline-modified cuprous oxide nanoparticle monolithic electrode for electrocatalytic reduction of carbon dioxide, and the preparation steps of the method are as follows:
[0007] Preparation of S1 polyaniline / carbon paper:
[0008] Pre-treating the carbon paper to obtain clean carbon paper;
[0009] The acid is diluted in an aqueous solution, and a certain volume of aniline is ultrasonically mixed with the acid solution to obtain an aniline electrolyte solution. The treated carbon paper is immersed in the electrolyte solution, and electrodeposition is performed on the cathode. After washing with deionized water and drying, polyaniline / carbon paper is obtained;
[0010] Preparation of S2 polyaniline / carbon paper supported Cu-BTC:
[0011] Weigh a certain amount of trimesic acid and dissolve it in ethanol solution, and dissolve it by ultrasonication;
[0012] Weigh a certain amount of copper acetate and dissolve it in water to form a copper acetate solution, place the solution in a 50-100°C environment and stir, and cool the solution to room temperature;
[0013] The prepared polyaniline / carbon paper was placed vertically in the above solution, a certain amount of polyvinyl pyrrolidone was added, and then the trimesic acid solution was slowly poured into the mixed solution and stirred at room temperature. A layer of Cu-BTC was uniformly grown on the surface of the polyaniline / carbon paper. After the above electrode was rinsed, it was dried at 60°C for 12h;
[0014] S3 low temperature activated polyaniline / carbon paper loaded cuprous oxide monolithic electrode:
[0015] The electrode with Cu-BTC uniformly loaded on the surface of the polyaniline / carbon paper is calcined in a nitrogen atmosphere to obtain a polyaniline / carbon paper loaded cuprous oxide monolithic electrode;
[0016] Furthermore, in step S1, the carbon paper pretreatment step is: 2 The carbon paper was placed in a methanol solution and ultrasonicated for 20 min, then placed in distilled water and ultrasonicated for 20 min, and the washing was repeated three times.
[0017] Optionally, in step S1, the acid includes: one or more of sulfuric acid, hydrochloric acid, and phosphoric acid, the acid concentration is 0.5-1.5 mol / L, the volume of aniline is 1 mol / L acid, and 13.5 mL of aniline solution is added.
[0018] Optionally, in step S1, the electrolyte solution is subjected to electrodeposition in the aniline electrolyte solution to obtain polyaniline / carbon paper, and the deposition conditions include: an initial voltage of 0.5-1.3 V, a deposition time of 50-400 s, a sampling interval of 0.1 s, a sensitivity of 1×10 -1 A, standing time is 0s;
[0019] Optionally, the mass of trimesic acid in step S2 is 0.1-0.4 g.
[0020] Optionally, in step S2, the mass of cupric acetate is 0.2-1.5 g, the stirring time is 1-4 h, and the mass of polyvinyl pyrrolidone is 0.05-0.75 g.
[0021] Optionally, in step S3, the flow rate of nitrogen is 2-5 mL, the calcination temperature is 200-400° C., the heating rate is 3-10° C. / min, and the calcination reaction time is 2-4 h.
[0022] Beneficial effects: The present invention provides a method for preparing a thermally activated polyaniline-modified cuprous oxide nanoparticle monolithic electrode for electrocatalytic reduction of carbon dioxide, which has the following advantages:
[0023] S1 uses an in-situ deposition method to grow a Cu-based catalyst on the catalyst surface to prepare an electrocatalytic carbon dioxide reduction electrode, which can avoid the use of additional binders and conductive agents, prevent the material from falling off due to the addition of binders, and reduce the cost of electrode preparation;
[0024] S2 utilizes the complexation between the polyaniline layer and copper ions to increase the loading amount of copper ions on the conductive substrate and the amount of catalytic activity, thereby improving the catalytic efficiency of the electrocatalytic electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A flow chart of the preparation method provided for an example of the present invention;
[0026] Figure 2 A scanning electron microscope image of a thermally activated polyaniline-modified cuprous oxide nanoparticle monolithic electrode provided by an example of the present invention;
[0027] Figure 3 This is the Faraday efficiency diagram of the thermally activated polyaniline modified cuprous oxide nanoparticle monolithic electrode. DETAILED DESCRIPTION
[0028] Example 1: Preparation method of thermally activated polyaniline modified cuprous oxide nanoparticle monolithic electrode
[0029] The carbon paper was pretreated to obtain clean carbon paper. 54 mL of sulfuric acid was poured into 1 L of deionized water for dilution. 13.5 mL of aniline was ultrasonically mixed with the above sulfuric acid solution to obtain an aniline electrolyte solution. The treated carbon paper was immersed in the electrolyte solution and electrodeposited on the cathode. The electrodeposition conditions were as follows: an initial voltage of 1 A, a deposition time of 100 s, a sampling interval of 0.1 s, and a sensitivity of 1 × 10 -1 A, after standing for 0 s, washing with deionized water and drying, polyaniline / carbon paper was obtained;
[0030] Weigh 0.2 g of trimesic acid and dissolve it in ethanol solution, and dissolve it by ultrasonication. Weigh 0.2 g of copper acetate and dissolve it in water to form a copper acetate solution, place the solution in a 100°C environment and stir, and cool the solution to room temperature;
[0031] The prepared polyaniline / carbon paper was placed vertically in the above solution, 0.1 g of polyvinyl pyrrolidone was added, and then the trimesic acid solution was slowly poured into the mixture, and stirred at room temperature. A layer of Cu-BTC was uniformly grown on the surface of the polyaniline / carbon paper. After rinsing the above electrode, it was dried at 60°C for 12 hours;
[0032] The polyaniline / carbon paper electrode uniformly loaded with Cu-BTC was calcined at 250° C. for 2 h in a nitrogen atmosphere to obtain a polyaniline / carbon paper loaded cuprous oxide monolithic electrode.
[0033] Example 2: Preparation method of thermally activated polyaniline modified cuprous oxide nanoparticle monolithic electrode
[0034] The difference between this embodiment and embodiment 1 is that the time of polyaniline deposition is different;
[0035] The carbon paper was pretreated to obtain clean carbon paper. 54 mL of sulfuric acid was poured into 1 L of deionized water for dilution, and 13.5 mL of aniline was ultrasonically mixed with the above sulfuric acid solution to obtain an aniline electrolyte solution. The carbon paper treated above was immersed in the electrolyte solution and electrodeposited on the cathode. The electrodeposition conditions were an initial voltage of 1 A, a deposition time of 50 s, a sampling interval of 0.1 s, and a sensitivity of 1×10 -1 A, after standing for 0 s, washing with deionized water and drying, polyaniline / carbon paper was obtained;
[0036] Weigh 0.2 g of trimesic acid and dissolve it in ethanol solution, and dissolve it by ultrasonication. Weigh 0.2 g of copper acetate and dissolve it in water to form a copper acetate solution, place the solution in a 100°C environment and stir, and cool the solution to room temperature;
[0037] The prepared polyaniline / carbon paper was placed vertically in the above solution, 0.1 g of polyvinyl pyrrolidone was added, and then the trimesic acid solution was slowly poured into the mixture, and stirred at room temperature. A layer of Cu-BTC was uniformly grown on the surface of the polyaniline / carbon paper. After rinsing the above electrode, it was dried at 60°C for 12 hours;
[0038] The polyaniline / carbon paper electrode uniformly loaded with Cu-BTC was calcined at 250° C. for 2 h in a nitrogen atmosphere to obtain a polyaniline / carbon paper loaded cuprous oxide monolithic electrode.
[0039] Example 3: Preparation method of thermally activated polyaniline modified cuprous oxide nanoparticle monolithic electrode
[0040] The difference between this embodiment and embodiment 2 is that the pyrolysis temperature of polyaniline is different;
[0041] The carbon paper was pretreated to obtain clean carbon paper. 54 mL of sulfuric acid was poured into 1 L of deionized water for dilution. 13.5 mL of aniline was ultrasonically mixed with the above sulfuric acid solution to obtain an aniline electrolyte solution. The treated carbon paper was immersed in the electrolyte solution and electrodeposited on the cathode. The electrodeposition conditions were as follows: an initial voltage of 1 A, a deposition time of 50 s, a sampling interval of 0.1 s, and a sensitivity of 1 × 10 -1 A, after standing for 0 s, washing with deionized water and drying, polyaniline / carbon paper was obtained;
[0042] Weigh 0.2 g of trimesic acid and dissolve it in an ethanol solution, dissolve it by ultrasonication, weigh 0.2 g of copper acetate and dissolve it in water to form a copper acetate solution, place the solution in an environment of 100° C. and stir, and cool the solution to room temperature;
[0043] The prepared polyaniline / carbon paper was placed vertically in the above solution, 0.1 g of polyvinyl pyrrolidone was added, and then the trimesic acid solution was slowly poured into the mixture, and stirred at room temperature. A layer of Cu-BTC was uniformly grown on the surface of the polyaniline / carbon paper. After rinsing the above electrode, it was dried at 60°C for 12 hours;
[0044] The polyaniline / carbon paper electrode uniformly loaded with Cu-BTC was calcined at 350° C. for 2 h in a nitrogen atmosphere to obtain a polyaniline / carbon paper loaded cuprous oxide monolithic electrode.
[0045] Example 4: Preparation method of thermally activated polyaniline modified cuprous oxide nanoparticle monolithic electrode
[0046] The difference between this embodiment and embodiment 3 is that the quality of polyvinyl pyrrolidone in the synthesis of Cu-BTC is different;
[0047] The carbon paper was pretreated to obtain clean carbon paper. 54 mL of sulfuric acid was poured into 1 L of deionized water for dilution. 13.5 mL of aniline was ultrasonically mixed with the above sulfuric acid solution to obtain an aniline electrolyte solution. The treated carbon paper was immersed in the electrolyte solution and electrodeposited on the cathode. The electrodeposition conditions were as follows: an initial voltage of 1 A, a deposition time of 100 s, a sampling interval of 0.1 s, and a sensitivity of 1 × 10 -1 A, after standing for 0 s, washing with deionized water and drying, polyaniline / carbon paper was obtained;
[0048] Weigh 0.2 g of trimesic acid and dissolve it in an ethanol solution, dissolve it by ultrasonication, weigh 0.2 g of copper acetate and dissolve it in water to form a copper acetate solution, place the solution in an environment of 100° C. and stir, and cool the solution to room temperature;
[0049] The prepared polyaniline / carbon paper was placed vertically in the above solution, 0.05 g of polyvinyl pyrrolidone was added, and then the trimesic acid solution was slowly poured into the mixed solution and stirred at room temperature. A layer of Cu-BTC was uniformly grown on the surface of the polyaniline / carbon paper. After the above electrode was rinsed, it was dried at 60°C for 12 hours;
[0050] The polyaniline / carbon paper electrode uniformly loaded with Cu-BTC was calcined at 350° C. for 2 h in a nitrogen atmosphere to obtain a polyaniline / carbon paper loaded cuprous oxide monolithic electrode.
[0051] Experimental Example 1
[0052] The electrode prepared in Example 2 was used for the electrocatalytic carbon dioxide reduction performance test. The cathode was the prepared integral electrode, the anode was a platinum sheet electrode, and the reference electrode was an Ag / AgCl electrode. The electrochemical reaction was carried out in an H-type reactor. The cathode chamber and the anode chamber were separated by a proton exchange membrane. Before the reaction, carbon dioxide gas was continuously introduced into the cathode chamber for 40 minutes. The electrocatalytic reduction reaction results were as follows: Figure 3 shown.
[0053] Depend on Figure 3 It can be seen that the integral electrode prepared in Example 2 has a good carbon dioxide reduction effect, wherein when the voltage is -0.98 V vs. RHE, the Faradaic efficiency of ethylene can reach 38%.
Claims
1. A method for preparing a thermally activated polyaniline-modified cuprous oxide nanoparticle monolithic electrode for electrocatalytic reduction of carbon dioxide, comprising the following steps: Preparation of S1 polyaniline / carbon paper: Pre-treating the carbon paper to obtain clean carbon paper; The acid is diluted in an aqueous solution, and a certain volume of aniline is ultrasonically mixed with the acid solution to obtain an aniline electrolyte solution. The treated carbon paper is immersed in the electrolyte solution, and electrodeposition is performed on the cathode. After washing with deionized water and drying, polyaniline / carbon paper is obtained; Preparation of S2 polyaniline / carbon paper supported Cu-BTC: Weigh a certain amount of trimesic acid and dissolve it in ethanol solution, and dissolve it by ultrasonication; Weigh a certain amount of copper acetate and dissolve it in water to form a copper acetate solution, place the solution in a 50-100°C environment and stir, and cool the solution to room temperature; The prepared polyaniline / carbon paper was placed vertically in the above solution, a certain amount of polyvinyl pyrrolidone was added, and then the trimesic acid solution was slowly poured into the mixed solution and stirred at room temperature. A layer of Cu-BTC was uniformly grown on the surface of the polyaniline / carbon paper. After the above electrode was rinsed, it was dried at 60°C for 12h; S3 low temperature activated polyaniline / carbon paper loaded cuprous oxide monolithic electrode: The polyaniline / carbon paper electrode uniformly loaded with Cu-BTC on its surface is pyrolyzed in a nitrogen atmosphere to obtain a polyaniline / carbon paper loaded cuprous oxide monolithic electrode.
2. The method for preparing the heat-activated polyaniline-modified cuprous oxide nanoparticle monolithic electrode according to claim 1, characterized in that: In the step S1, the acid includes one or more of sulfuric acid, hydrochloric acid, and phosphoric acid, the acid concentration is 0.5-1.5 mol / L, and the volume of aniline is 6-21 mL.
3. The method for preparing the heat-activated polyaniline-modified cuprous oxide nanoparticle monolithic electrode according to claim 1, characterized in that: In the step S1, the electrolyte solution is subjected to electrodeposition in the aniline electrolyte solution to obtain polyaniline / carbon paper. The deposition conditions include: an initial voltage of 0.5-1.3A, a deposition time of 50-400s, a sampling interval of 0.1s, a sensitivity of 1×10 -1 A, the standing time is 0s.
4. The method for preparing the thermally activated polyaniline modified cuprous oxide nanoparticle monolithic electrode according to claim 1, characterized in that: The mass of trimesic acid in step S2 is 0.1-0.4 g.
5. The method for preparing the thermally activated polyaniline modified cuprous oxide nanoparticle monolithic electrode according to claim 1, characterized in that: In the step S2, the mass of cupric acetate is 0.2-1.5 g, the stirring time is 1-4 h, and the mass of polyvinyl pyrrolidone is 0.05-0.75 g.
6. The method for preparing the thermally activated polyaniline modified cuprous oxide nanoparticle monolithic electrode according to claim 1, characterized in that: In step S3, the calcination temperature is 200-400° C., the heating rate is 3-10° C. / min, the flow rate of nitrogen is 2-5 mL, and the calcination reaction time is 2-4 h.
7. A method for preparing a thermally activated polyaniline modified cuprous oxide nanoparticle monolithic electrode prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The preparation method of the thermally activated polyaniline-modified cuprous oxide nanoparticle monolithic electrode can be used in the field of electrochemical reduction technology.
Citation Information
Patent Citations
Polyanline-cuprous oxide composite as well as preparation method and application thereof
CN108130552A
Copper-containing nanoparticles and manufacturing method therefor
US20110193034A1
METHOD FOR ASSEMBLING AND SYNTHESIZING Cu2O PARTICLE-SUPPORTED POROUS CuBTC
US20210178362A1